2016
DOI: 10.1038/srep33510
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of transcription in castration-resistant prostate cancer cells uncovers active enhancers and direct androgen receptor targets

Abstract: Androgen receptor (AR) is a male sex steroid-activated transcription factor (TF) that plays a critical role in prostate cancers, including castration-resistant prostate cancers (CRPC) that typically express amplified levels of the AR. CRPC-derived VCaP cells display an excessive number of chromatin AR-binding sites (ARBs) most of which localize to distal inter- or intragenic regions. Here, we analyzed direct transcription programs of the AR in VCaP cells using global nuclear run-on sequencing (GRO-seq) and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 52 publications
3
23
1
Order By: Relevance
“…A further elucidation of direct AR target genes has been performed by combining AR chromatin-binding profiles with gene expression profiling. Upon androgen stimulation, hundreds to thousands of genes are being either up-or downregulated, dependent on hormone stimulation times and bioinformatics cut-offs used (DePrimo et al 2002, Hendriksen et al 2006, Massie et al 2011, Toropainen et al 2016. Apart from protein-coding genes, non-coding transcripts are also under direct control of AR (Wang et al 2011, Toropainen et al 2016.…”
Section: How To Identify Ar Target Genes?mentioning
confidence: 99%
See 1 more Smart Citation
“…A further elucidation of direct AR target genes has been performed by combining AR chromatin-binding profiles with gene expression profiling. Upon androgen stimulation, hundreds to thousands of genes are being either up-or downregulated, dependent on hormone stimulation times and bioinformatics cut-offs used (DePrimo et al 2002, Hendriksen et al 2006, Massie et al 2011, Toropainen et al 2016. Apart from protein-coding genes, non-coding transcripts are also under direct control of AR (Wang et al 2011, Toropainen et al 2016.…”
Section: How To Identify Ar Target Genes?mentioning
confidence: 99%
“…Of note, the number of genome-wide AR-binding sites is considerably higher than the number of differentially expressed genes upon androgen stimulation. Moreover, merely 30% of the AR-bound enhancers show eRNA production (Toropainen et al 2016). This suggests that only a fraction of AR-bound enhancers are functional or that these enhancers can function without eRNA transcription.…”
Section: How To Identify Ar Target Genes?mentioning
confidence: 99%
“…It has been argued that redistribution of limiting amounts of specific co-regulators from one set of enhancers to another is a unifying explanation for rapid repression in association with transcriptional induction (Guertin et al 2014;Schmidt et al 2016), which has been observed in a variety of other signaling contexts (Hah et al 2011;Step et al 2014;Franco et al 2015;Loft et al 2015;Toropainen et al 2016). Although redistribution of FOXA1 occupancy with glucocorticoid treatment has been reported (Swinstead et al 2016), whether specific transcription factors or co-activators rapidly redistribute their nuclear position from repressed to activated regulatory elements in association with GR activation has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is often difficult to identify which of these transcripts are directly regulated by AR, largely due to the fact that AR often binds to enhancers that are distal to its target genes (Wang et al 2007). Carefully assessing the temporality of androgenmediated gene regulation (Massie et al 2011), integrating transcriptomic data with AR cistromes (Pomerantz et al 2015) and/or using more sophisticated transcriptomic techniques such as global run-on sequencing (GRO-seq) (Toropainen et al 2016), which is designed to identify nascent transcription, have improved the detection of bona fide AR targets in PCa cell lines and tissues. Nevertheless, accurately differentiating direct vs indirect targets of the AR remains challenging.…”
Section: Androgen Receptor-mediated Rewiring Of Microrna/mrna Transcrmentioning
confidence: 99%